Pengaruh Iklan, Electronic Word Of Mouth, Dan Kesadaran Merek Terhadap Niat Beli Pada Produk Skincare - Wulandari, Rani; Febrilia, Ika; Rahmi, Rahmi (Fakultas Ekonomi Universitas Gresik, 2023)
This research aims to determine the effect of Advertising, Electronic Word of Mouth, and Brand Awareness on Purchase Intentions in Skincare Products. The method used in this research is a quantitative method with non-probability sampling techniques, especially purposive sampling. The reachable population in this study were internet users who had seen information on skincare for the Scarlett Whitening brand on social media with a total of 216 respondents. The data analysis technique used is descriptive statistics, data quality test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The result of this study is that the advertising variable has a significant positive effect on purchase intention. Electronic word of mouth (EWOM) has a significant positive effect on purchase intention. Brand awareness has a significant positive effect on purchase intention.